Organocatalytic enantioselective transformations involving quinone derivatives as reaction partners. Issue 6 (7th February 2018) - Zhang, Xiao; Chen, Ye-Hui; Tan, Bin
Graphical abstract: Highlights: Organocatalytic asymmetric reactions involving quinone derivatives were summarized. The roles of quinones as donors and acceptors were investigated. Several types of chiral catalyst were employed. Abstract: This digest summarizes the recent progress made in the organocatalytic asymmetric reactions involving 1, 4-quinone derivatives. The roles of quinones as Michael donors, Michael acceptors, dienophiles, 1, 3-dipolarophiles and cascade reaction partners have been extensively investigated to access complex structural frameworks in the presence of chiral amine catalysts, phosphoric acid catalysts, bifunctional catalysts (Cinchona alkaloids- and thiourea-based), carboxylic acid catalysts, boronic acid catalysts and cationic oxazaborolidinium ions.